Determination of Chemical Composition and Nutritional Values of Moringa oleifera Leaves - Yameogo, Charles Windepagnagde; Bengaly, Marcel Daba; Savadogo, Aly; Nikiema, Philippe Augustin; Traore, Sabadenedyo Alfred (Pakistan Journal of Nutrition, 2011)
The study on chemical composition and nutritional values of Moringa oleifera leaves has been carried out by analysing samples of this plant leaves collected from three different sectors of Ouagadougou. The analysis of nutrients contents including elemental has been done using recommended method of analysis. The result of analysis shows that the percentages (%) of proteins, moisture, fat, carbohydrate of the leaves are respectively 11.9; 73.9; 1.1 and 10.6% for the cool matter. For the dry matter, the contents in proteins, moisture, fat and carbohydrate are respectively 27.2; 5.9; 17.1 and 38.6%. The result of the mineral composition expressed in mg for 100 g of matters are 847.1; 151.3; 549.6; 17.5; 1.3 and 111.5 in the cool matter respectively for the Calcium, Magnesium, Potassium, Iron, Zinc and Phosphor. The contents of same minerals analyzed for the dry matter are respectively 2098.1; 406.0; 1922.0; 28.3; 5.4 and 351.1. The result showed a satisfactory composition and a significant variability between the nutrients contents of different sectors. This plant can be valorized for a balanced nutrition of populations.